Engineered T Cell Therapy for Cancer in the Clinic - Zhao, Lijun; Cao, Yu J. (Frontiers in Immunology, 2019)
T cells play a key role in cell-mediated immunity, and strategies to genetically modify T cells, including chimeric antigen receptor (CAR) T cell therapy and T cell receptor (TCR) T cell therapy, have achieved substantial advances in the treatment of malignant tumors. In clinical trials, CAR-T cell and TCR-T cell therapies have produced encouraging clinical outcomes, thereby demonstrating their therapeutic potential in mitigating tumor development. This article summarizes the current applications of CAR-T cell and TCR-T cell therapies in clinical trials worldwide. It is predicted that genetically engineered T cell immunotherapies will become safe, well-tolerated and effective therapeutics and bring hope to cancer patients.